Pembelajaran Public Speaking di Pondok Pesantren untuk Moderasi Indonesia - Uus Uswatusolihah (KOMUNIKA: Jurnal Dakwah dan Komunikasi, 2017)
This study focused on public speaking learning process for Indonesian moderation located at An Najah, Al Amin and Darussalam as pesantren partners of IAIN Purwokerto. Public Speaking learning process in pesantren has been conducted for long period of time and it has distinctive characters to be studied. This study is using explorativephenomenological methodology to uncovered this learning process. Data is collected using observation, interview and documentation. Result shows that public speaking and speaking techniques in general is mandatory subject for An Najah, Al Amin dan Darussalam. The objectives of Public speaking learning in those three pesantren is that the students could conveyed Islamic value and religion effectively. Public speaking is conducted in many methods and activities, such as muhadharah, discussion, role play on many programs and events where santri has responsibilities and authority for managing the process. There are differences in practising muhadharah on those three pesantrens. There are also workshops hosted by experts. With that the process of public speaking learning is more in practical way without theoretical-conceptual background. This results in public speaking theoretical concepts is rarely mastered, whereas pesantren is well known for its rich oral speech tradition.